Diabetes induces mitochondrial dysfunction and alters cholesterol homeostasis and neurosteroidogenesis in the rat cerebral cortex. Issue 178 (April 2018) - Romano, Simone; Mitro, Nico; Giatti, Silvia; Diviccaro, Silvia; Pesaresi, Marzia; Spezzano, Roberto; Audano, Matteo; Garcia-Segura, Luis Miguel; Caruso, Donatella; Melcangi, Roberto Cosimo
Highlights: One month of diabetes alters steroidogenic machinery in the cerebral cortex. Impaired cholesterol homeostasis was detected in the cerebral cortex of diabetic rats. Mitochondrial functionality was affected in the cerebral cortex of diabetic rats. Abstract: The nervous system synthesizes and metabolizes steroids (i.e., neurosteroidogenesis). Recent observations indicate that neurosteroidogenesis is affected by different nervous pathologies. Among these, long-term type 1 diabetes, together with other functional and biochemical changes, has been shown to alter neuroactive steroid levels in the nervous system. Using an experimental model of type 1 diabetes (i.e., streptozotocin injection) we here show that the levels of these molecules are already decreased in the rat cerebral cortex after one month of the initiation of the pathology. Moreover, decreased levels of free cholesterol, together with alterations in the expression of molecules involved in cholesterol biosynthesis, bioavailability, trafficking and metabolism were detected in the rat cerebral cortex after one month of diabetes. Furthermore, mitochondrial functionality was also affected in the cerebral cortex and consequently may also contribute to the decrease in neuroactive steroid levels. Altogether, these results indicate that neurosteroidogenesis is an early target for the effect of type 1 diabetes in the cerebral cortex.